Bankruptcy laws and debt renegotiation - Kolecek, Ludek (Journal of Financial Stability, 2008)
This paper analyzes the effect of the toughness of bankruptcy law on the number of liquidations in a simple model of borrowing and lending with asymmetric information, where the creditor cannot credibly commit to liquidate the firm if the default occurs. In our setting we consider a bankruptcy law to be a one-dimensional variable that influences creditor's expectation value of collateral. We find that there is an interval of the bankruptcy law, where the number of liquidations decreases in the toughness of the bankruptcy law. We also find that if the liquidation costs are high, softer bankruptcy law is preferred.